THE ANALYSIS OF CONCENTRATION IN THE BANKING SECTOR OF SERBIA IN THE POST-CRISIS PERIOD - Filipović, Maja; Avramović, Vladislava; Račić, Željko (International Journal of Economic Practice and Policy, 2017)
The objectives of this study are theoretical overview of coefficients which are commonly used to analyze the level of market concentration, as well as the analysis of  concentration of the banking market in the Republic of Serbia. The survey covers coefficient related to concentration ratios (CR5) and the Herfindahl - Hirschman's Index (HHI), during the period from 2008 to 2014. The results support the conclusion that the domestic banking market has a low concentration (overall), but that the trend of growth of top 5 banks participation in the total balance sheet of the sector which threatens to endager the development of competition in the future.